Modulation of signaling pathways by DJ-1: An updated overview - Neves, Margarida (2022)
Efforts have been made to understand the physiological and pathological role of DJ-1, a Parkinson's disease (PD)-associated protein, to provide new insights into PD pathophysiology. Such studies have revealed several neuroprotective roles of DJ-1, from which its ability to modulate signaling pathways seems to be of utmost importance for cell death regulation by DJ-1. Indeed, research on these topics has led to a higher number of publications disclosing a variety of mechanisms through which DJ-1 is able to modulate signaling pathways in distinct disease-related contexts. Thus, this graphical review presents the most relevant findings concerning the mechanisms through which DJ-1 exerts its regulatory activity on signaling cascades relevant for DJ-1 neuroprotective action, namely ERK1/2, PI3K/Akt, and ASK1 pathways, and Nrf2 and p53 transcription factors-related signaling. A greater focus was given to perform an overview of the research interests over the last years, especially in the most recent works, to highlight the current research lines in this topic, and point out future directions in the field. In addition, the impact of DJ-1 mutations causative of PD and the importance of the redox status of DJ-1's cysteine residues for the action of DJ-1 on signaling modulation was also addressed to uncover the potential pathological mechanisms associated with loss of DJ-1 native function.